ANALISIS PENGEMBANGAN POTENSI DESA WISATA MELALUI OPTIMALISASI ASSET BASED COMMUNITY DEVELOPMENT DI DESA MOJOKAMBANG - Hidayati Amelia Rahayu; Istikhomah Istikhomah; Ninda Fatmawati; Rodhiyahtul Warda Usami; Fungki Ulan Dari; Muhammad Alhada Fuadilah Habib (Universitas Nahdlatul Ulama Sidoarjo, 2022)
This study aims to identify and analyze community empowerment programs using the ABCD (asset based community development) approach or theory to develop the potential of tourism villages in Mojokambang Village. This study uses a qualitative approach, the source of the data obtained in this study comes from primary and secondary data. Primary data was obtained through the interview process, while secondary data came from books and journals that support the research results. The results showed that Mojokambang Village has potential assets to be developed into a tourist village through optimizing the management of the “jogo kali” park. Development efforts are carried out through an empowerment program based on the results of data identified with the ABCD approach. Directly or indirectly, the empowerment program carried out by the manager together with all stakeholders has had a positive impact on the economic welfare of the empowered community, starting from the economic, psychological, and social aspects. The empowerment program that was carried out was running quite optimally and had a positive impact on empowered communities before the COVID-19 pandemic. However, during a pandemic, the park's operational activities and empowerment programs went into a vacuum, giving rise to several social phenomena and potential problems. However, with the improving situation of the COVID-19 pandemic, park managers and residents of Mojokambang Village are again aggressively activating the operational activities of the